Metalorganic vapor phase epitaxial growth of AlGaN directly on reactive-ion etching-treated GaN surfaces to prepare AlGaN/GaN heterostructures with high electron mobility (∼1500 cm2 V−1 s−1): Impacts of reactive-ion etching-damaged layer removal. (25th October 2018) - Yamamoto, Akio; Kanatani, Keito; Makino, Shinya; Kuzuhara, Masaaki
Abstract: In this paper, we report the impact of the HCl treatment of reactive-ion-etching-treated GaN (RIE-treated GaN) surfaces in fabricating AlGaN/GaN structures by regrowing an AlGaN layer directly on the RIE-treated GaN surfaces. By dipping RIE-treated GaN surfaces into a hot HCl solution, a 10–30-nm-thick surface layer, which corresponded to the damaged layer, was etched off. After the annealing of the HCl-treated GaN in NH3 + H2 atmosphere, a 30-nm-thick Al30 Ga70 N layer was grown on it. The HCl treatment resulted in a decrease in dotlike defect density observed on the AlGaN/GaN surfaces and a marked improvement of electrical data of AlGaN/GaN structures. A clear dependence of electron mobility on sheet carrier concentration was observed, and the highest electron mobility obtained was increased to ∼1500 cm 2 V −1 s −1 . High-electron-mobility transistors (HEMTs) with excellent performances were successfully fabricated by employing the HCl treatment and metal–insulator–semiconductor (MIS) gate structures.